Marine Carotenoids in Inflammation and Cancer - Talero, Elena; Ávila-Román, Javier (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue covers both the in vitro and in vivo evaluation of marine carotenoids with anti-inflammatory and anticancer activities as well as clinical trials conducted in humans. Among the properties of carotenoids discussed in this book, it is worth highlighting the potential of astaxanthin and its precursor metabolite, adonixanthin, since oral administration of these carotenoids has shown beneficial effects on glioblastoma for the first time by suppressing cell proliferation and migration. In addition, astaxanthin has been shown to inhibit Helicobacter pylori-induced gastric carcinoma cell motility and, consequently, cancer progression through the inhibition of cytoskeleton reorganization. In addition, a carotenoid-containing lipid extract of Gloeothece sp. has demonstrated antioxidant, anti-inflammatory, and anticancer properties in vitro.